Analysis of the Technology Acceptance Theoretical Model in Examining Users’ Behavioural Intention to Use an Augmented Reality App (IMAPCampus) - Hamed Alqahtani; Manolya Kavakli; Nazim Uddin Sheikh (International Journal of Engineering and Management Research, 2018)
As technology penetrates into our lives, the vital need for institutions to provide rapid access to information has grown. Recently, Augmented Reality (AR) has emerged as a technology for educational institutions to enhance users’ experience by overlaying computational information into their reality. iMAP_CampUS is a mobile AR application showing campus-related information superimposed on a map of Macquarie University. Using iMAP_CampUS app, our goal is to investigate the factors influencing the acceptance of a typical mobile AR system. The thesis proposes a theoretical framework with 14 research hypotheses based on UTAUT, IS success factors and Motivation theory. This framework is empirically examined using web-based survey data from a sample of 86 users. We use Structural Equation Modeling (SEM) and Partial Least Squares (PLS) to evaluate the acceptance and behavioural intention to use iMAP-CampUS app. The results indicate that ten research hypotheses have been significantly supported, while four have been rejected. The findings state that perceived enjoyment and user’s satisfaction are important determinants for the use of iMap-CampUS. However, performance expectancy has not demonstrated any significant impacts on behavioural intention to use the app.